Gene Therapy in Modern Medicine: Promises and Challenge in Treating Genetic Diseases - Pritam Kumar Saini (International Journal of Genetic Modifications and Recombinations, 2024)
Gene therapy is a medical approach that focuses on altering or adjusting an individual’s genes to treat or prevent illnesses. The aim is to repair faulty genes or insert new ones into the body to combat diseases. Gene therapy can involve directly introducing modified or new genes into a patient’s cells or altering the genes already present in the patient’s body. This approach shows potential for treating a range of conditions, including genetic disorders like cystic fibrosis and sickle cell anemia, as well as certain forms of cancer. Although gene therapy has shown promise in clinical trials, challenges, such as delivery methods, immune responses, and ethical considerations remain significant obstacles to its widespread use. Modern medicine has witnessed transformative advancements, particularly in the field of gene therapy, a cutting-edge approach aimed at treating or potentially curing genetic disorders at their source. Unlike traditional treatments that focus on managing symptoms, gene therapy targets the root cause of disease by correcting or modifying defective genes within a patient’s cells. Techniques, such as viral vector delivery, CRISPR-Cas9, and RNA-based therapies enable precise alterations in the genetic code, offering hope for inherited disorders, cancers, and even infectious diseases. Recent clinical successes, including treatments for spinal muscular atrophy, hemophilia, and certain forms of blindness, highlight gene therapy’s potential to reshape therapeutic approaches. Despite these advancements, significant challenges persist in guaranteeing the safety, effectiveness, and worldwide accessibility of gene therapies. Issues, such as immune responses to vectors, ethical concerns, high treatment costs, and regulatory complexities pose significant obstacles. However, ongoing research and advances in genome-editing technology, vector design, and delivery systems continue to enhance the safety and scope of gene therapy, paving the way for broader applications in modern medicine, and a new era of personalized, precision healthcare.
Keywords: CRISPR-Cas9; Gene Editing; adenovirus vectors; gene delivery; genetic disorders; lentivirus vectors; somatic gene therapy